Systemy sztucznej inteligencji w procesach administracyjnych i w pracy urzędów patentowych na świecie – przegląd wybranych inicjatyw oraz analiza dalszego ich rozwoju w kontekście zasad etycznych dla sztucznej inteligencji : część 1 - Matczuk, Joanna; Pilecka, Adrianna (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2024)
Advanced technologies, such as artificial intelligence, are gaining increasing importance in the operations of offices worldwide, including intellectual property offices. This article discusses the development and various uses of artificial intelligence by offices such as EUIPO, USPTO and WIPO, including specific tools employed by these offices and made available to users, automation of processes related to industrial property rights registration, analysis of relevant data sets in the context of trademark searches or patent research. It also presents the challenges and benefits from the integration of modern technologies in the context of intellectual property protection.
Keywords: AI; artificial intelligence; intellectual property offices; intellectual property; industrial property; administrative procedure